RANCANG BANGUN SISTEM INFORMASI AKUNTANSI PERSEDIAAN BARANG PERTANIAN PADA DIREKTORAT JENDERAL HORTIKULTURA - Endang Pujiastuti - STMIK Nusa Mandiri; Dahlia .; Asty Melinda; Sapitri - UBSI (SPEED - Sentra Penelitian Engineering dan Edukasi, 2020)
Abstract - The use of information system technology in an era like this has become very important for agencies that need an accurate, reliable, fast, relevant and detailed information flow. Agricultural information inventory systems available at the Directorate General of Horticulture, Ministry of Agriculture are still carried out manually, starting from recording incoming goods, recording outgoing goods, and making reports, making it possible during the process of error occurs in the search for necessary data. The best solution to solve existing problems is to create a web-based agricultural inventory application because it is better than manual system recording. That way recording and information will be faster and easier so that it can improve performance at the Directorate General of Horticulture, Ministry of Agriculture. This study aims to get an overview of the inventory system information, what problems arise and how to design a suitable agricultural inventory system as a proposed problem in the inventory of agricultural goods in the Directorate General of Horticulture, Ministry of Agriculture. To get a new inventory information system, an analysis and design of the system is carried out on the current inventory system. Design and Development of Agricultural Inventory Accounting Information System is supported by using PHP (Hypertext Prepocessor), Javacript, CSS (Cascanding Style Sheet), Xampp, HTML (HyperText Markup Language), and MySQL Database. It is hoped that the application of the supply of agricultural goods will benefit the Directorate General of Horticulture, Ministry of Agriculture.Keywords: Design of Accounting Information Systems, Inventory Accounting Information Systems. Abstrak - Penggunaan teknologi sistem informasi di zaman seperti ini menjadi sangat penting bagi instansi yang membutuhkan aliran informasi yang akurat, terpercaya, cepat, relevan dan detail. Sistem informasi persediaan barang pertanian yang ada pada Direktorat Jenderal Hortikultura Kementerian Pertanian masih dilakukan secara manual, mulai dari pencatatan barang masuk, pencatatan barang keluar, dan pembuatan laporan, sehingga memungkinkan pada saat proses berlangsung terjadi kesalahan dalam pencarian data-data yang diperlukan. Solusi yang terbaik untuk memecahkan permasalahan-permasalahan yang ada yakni dengan membuat aplikasi persediaan barang pertanian berbasis web karena lebih baik daripada pencatatan sistem yang manual. Dengan begitu pencatatan dan informasi akan lebih cepat dan mudah sehingga dapat meningkatkan kinerja pada Direktorat Jenderal Hortikultura Kementerian Pertanian. Penelitian ini bertujuan untuk mendapatkan gambaran sistem informasi persediaan barang, permasalahan apa yang timbul dan bagaimana merancang sistem persediaan barang pertanian yang sesuai sebagai usulan permasalahan pada kegiatan persediaan barang pertanian Direktorat Jenderal Hortikultura Kementerian Pertanian. Untuk mendapatkan sistem infromasi persediaan yang baru maka dilakukan analisis dan desain sistem pada sistem persediaan yang berjalan. Rancang Bangun Sistem Informasi Akuntansi Persediaan Barang Pertanian ini didukung dengan menggunakan PHP (Hypertext Prepocessor), Javacript, CSS (Cascanding Style Sheet), Xampp, HTML (HyperText Markup Language), dan Database MySQL. Sehingga diharapkan aplikasi persediaan barang pertanian ini bermanfaat bagi Direktorat Jenderal Hortikultura Kementerian Pertanian.Kata Kunci: Rancang Bangun Sistem Informasi Akuntansi, Sistem Informasi Akuntansi Persediaan.